Factors Affecting the Language Learning of EFL Students Through ABC Model: A Cross Cultural Analysis - Sariani Sariani; Mutia El Khairat (Politeknik Negeri Padang, 2016)
This research concerns on a breakthrough in enhancing the learning by having more understanding between the studentsand lecturers. It is in basis of one experience is un-comparable to another experience as each has their own uniqueness. Regarding tothis matter, the use of ABC’s model, as has been experienced by other studies, is considered significant to reach the goal of thisresearch. This study applies qualitative method based on the descriptive data, and are analyzed by using cultural analysis ofdifferences and similarities taken from the ‘Venn Diagram’ between autobiographies of the participants and biographies of theirpartner. The participants were randomly chosen from fresh year students at English Department, State Polytechnic of Padang. Theyare from different family backgrounds; middle up family level and low family level. Derived from the ABC analysis conducted, thereare five factors found which are considered to affect EFL students in learning process; those are passion in learning English, learningprocess, motivation, facilities, and circumstances.